Whether the Sign of Prostration in the Face of Believers is Real? the Qur’an’s Victory Verses and Its Biblical Reference - Shofaussamawati, Shofaussamawati; Haqqi, Muhammad Nashrul (HERMENEUTIK : Jurnal Ilmu al-Qur'an dan Tafsir, 2023)
This article attempts to understand the meaning of the sign of prostration in surah 48.29. What is the exact meaning of athar al-sujūd sign of prostration? The Intertextuality approach is used in this paper. The phrase athar al-sujūd mentioned only once in the Qur'an. Ibn Manẓūr (d. 1311) says that the word athar means the traces of a thing al-Aṣfahānī (d. 1109) adds that the word ignifies an effect which is represented by an existence, whether abstract or material. Often, the word is oriented to the past. The word also means the influence or honour of the human soul and morality in which it is abstract. The word athar refers to something material, especially concerning the story of Moses. The story of the people in Moses' time in surah 40.21 illustrates that they have powers (ashadda minhum quwwa) and traces on earth (ātharan fī al-arḍ). In surah 18.64, the word athar refers to the trail of Moses’ journey with a young man (āthārihimā qaṣaṣa) while looking for a place where two seas meet (majma’ al-baḥrayn). The Muslim Scholar interprets the phrase sign of prostration in verse in an abstract context. Muqātil b. Sulaymān interprets it as a good guide and path (al-hudā wa al-simt al-ḥasan). It is similar to al-Thabarī and Ibn Kathīr, who interpret it as devoutness (khushū'). Al-Qāsimī has two interpretations: First, that is a good path or devoutness, as the early commentators say. Second, the traces of the soil (tharā al-arḍ) on the face. The Qur'an chooses the word sujūd to represent devoutness and modesty in worship. Artikel ini mencoba mencoba memaknai tanda sujud pada surat 48.29. Apa arti sebenarnya dari tanda sujud athar al-sujūd? Pendekatan Intertekstualitas digunakan dalam makalah ini. Ungkapan athar al-sujūd hanya disebutkan satu kali dalam Al-Qur'an. Ibnu Manẓūr (w. 1311) mengatakan bahwa kata athar berarti jejak-jejak sesuatu, al-Aṣfahānī (w. 1109) menambahkan bahwa kata tersebut menyulut suatu akibat yang diwakili oleh suatu wujud baik abstrak maupun material. Sering kali, kata itu berorientasi ke masa lalu. Kata itu juga berarti pengaruh atau kehormatan jiwa manusia dan moralitas yang di dalamnya bersifat abstrak. Kata athar mengacu pada sesuatu yang bersifat material, khususnya yang berkaitan dengan kisah Musa. Kisah umat pada zaman Musa dalam surat 40.21 menggambarkan bahwa mereka memiliki kekuatan (ashadda minhum quwwa) dan jejak di bumi (ātharan fī al-arḍ). Dalam surat 18.64, kata athar mengacu pada jejak perjalanan Musa dengan seorang pemuda (āthārihimā qaṣaṣa) saat mencari tempat bertemunya dua lautan (majma' al-baḥrayn). Ulama Muslim menafsirkan frase yang menandakan sujud dalam ayat tersebut dalam konteks abstrak. Muqatil b. Sulaymān mengartikannya sebagai petunjuk dan jalan yang baik (al-hudā wa al-simt al-ḥasan). Hal ini senada dengan al-Thabarī dan Ibn Kathīr yang mengartikannya sebagai ketakwaan (khushū'). Al-Qāsimī memiliki dua tafsir: Pertama, itu adalah jalan yang baik atau kesalehan seperti yang dikatakan para mufassir awal. Kedua, bekas tanah (tharā al-arḍ) di wajah. kata sujūd dipilih oleh Al-Qur'an untuk mewakili kesalehan dan kesopanan dalam beribadah.